2017
DOI: 10.5530/ijper.51.3s.21
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Chemical Composition Screening of Epilobium montanum Root

Abstract: Medical herbs have many bioactive component and they are used in microbial treatment since ancient time. The resistance of pathogen to antibiotic is became a critical problem, so novel antimicrobial agent related research is required. Epilobium montanum related antimicrobial research doesn't exist, therefore root of this medicinal plant investigation was applied against 17 bacteria and 1 fungi by using disk diffusion method. These microbial species include Bacillus, Enterobacter, Enterococcus, Escherichia, Kle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…Seventeen major chemical components were identified by GC-MS in ethanol extracts of E. montanum by Canli et al, wherein a large group of identified compounds was fatty acids (palmitic acid and (Z,Z,Z) 9,12,15-octadecatrienoic acid). Other significant compounds of the extract observed by these authors were: γ-sitosterol, 1-heptacosanol, and 1,2,3-benzenetriol [ 36 ]. Several compounds belonging to the terpenes group, i.e., camphor and α- and β-caryophyllene oxide, were found in our study; they were also observed in E. hirsutum and E. angustifolium by others [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen major chemical components were identified by GC-MS in ethanol extracts of E. montanum by Canli et al, wherein a large group of identified compounds was fatty acids (palmitic acid and (Z,Z,Z) 9,12,15-octadecatrienoic acid). Other significant compounds of the extract observed by these authors were: γ-sitosterol, 1-heptacosanol, and 1,2,3-benzenetriol [ 36 ]. Several compounds belonging to the terpenes group, i.e., camphor and α- and β-caryophyllene oxide, were found in our study; they were also observed in E. hirsutum and E. angustifolium by others [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For determination of the chemical composition of oil samples the methodology mentioned previously was used (Canlı, Yetgin, Akata & Altuner, 2017b).…”
Section: Determination Of Chemical Composition By Gc-msmentioning
confidence: 99%
“…The antimicrobial activity is determined using a disk diffusion method based on Andrews . Petri dishes with a diameter of 9 mm, which contained 25 mL of Mueller‐Hinton agar, were used in order to standardize the work, as described previously in several studies . The newly synthesized 1,3,4‐thiadiazole derivatives were dissolved in ethanol to a final concentration of 5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%